ANALISIS SISTEM UNIT PELAYANAN JASA ALSINTAN (UPJA) DI KECAMATAN KUALA KAMPAR KABUPATEN PELALAWAN - Febri Yeni; Novia Dewi (UIR Press, 2014)
The purpose of this research is to analyse usage of farm equipment and machinery managed by group of UPJA and its impact on economic expansion of society. The research was conducted in district of Kuala Kampar Pelalawan Regency. Data and information obtained from field survey and also instansional tracing were then analysed descriptively through tabulation method. The results indicated that organization of UPJA group was led by a manager and assisted by some operators who had task to operate farm equipment and mashinery with three divisions. Divisions consisted of division operational who direct some operators, technical division and division administration who assist manager in the case of management and financial book keeping of UPJA group. The analyss results showed that pay back of power thresher was 1,1 year, reaper 2,1 year, and dryer 1,5 year. The impact of development of UPJA were to increase opportunity of working and business activities, land efficiency, handling of post-harvest and acceleration of technology transfer. The problems associated to development of UPJA are low human resource and capital resource, location far from downtown, crop pattern in study area which generally is still once one year.